A polyacrylic acid sodium thickening agent with shear thinning and salt tolerance and a preparation method thereof
Patent Information
- Application Number
- CN202610046916.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-01-14
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-01-14
AI Technical Summary
[0005]针对现有聚丙烯酸钠增稠剂普遍耐盐性不佳、高耐盐技术中剪切稀释性不足、功能整合与核心性能难以协同等问题,本发明的目的在于提供一种具备剪切稀释与耐盐性的聚丙烯酸钠增稠剂及其制备方法
1. 显著提升了耐盐稳定性:通过构建化学-物理双重网络,有效屏蔽了盐离子对聚电解质主链的攻击,使产品在含盐环境中仍能保持较高的粘度保留率,适用盐浓度范围更宽。2. 实现了智能流变调控:产品具备明显的剪切稀释性,利于加工施工,同时剪切力消除后能快速恢复粘度,兼顾了加工性能与应用稳定性。3. 工艺可行性与兼容性好:制备方法基于UV光聚合,条件温和、易于控制;所得产品在复杂应用体系(如乳液涂料)中表现出良好的相容性与储存稳定性,便于产业化推广。4. 功能可拓展性强:在维持核心耐盐与流变性能的基础上,可方便地引入保湿等功能组分,制备多功能复合产品,满足差异化需求。
Smart Images

Figure CN121699054B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer materials technology, specifically relating to a sodium polyacrylate thickener with shear dilution and salt resistance, and its preparation method. Background Technology
[0002] Sodium polyacrylate (SPO) is an important synthetic polymer thickener widely used in daily chemicals, coatings, textiles, and oil extraction. However, as an anionic polyelectrolyte, it is extremely sensitive to electrolyte salts, and its thickening ability decreases significantly in the presence of salt, severely limiting its application in salt-containing systems. To improve its salt resistance, existing technologies typically employ copolymerization modification, the introduction of hydrophobic associative structures, or the synthesis of zwitterionic polymers, but these methods generally suffer from problems such as complex processes, high costs, or the introduction of special monomers.
[0003] Chinese invention patent CN 119371581 A (prior document 1) discloses a method for preparing a high-viscosity, salt-resistant sodium polyacrylate thickener by polymerization under ultraviolet light using sodium sulfite (Na2SO3) as a single initiator. While this method provides a relatively simple synthetic route, it still has the following significant limitations: First, the resulting product exhibits significant viscoelasticity and a "pole-climbing" phenomenon, with its rheological behavior leaning towards shear thickening or lacking controllable shear dilution. This can easily lead to difficulties in application scenarios requiring good processing fluidity, such as paint spraying and colloid delivery, resulting in problems like poor leveling. Second, when a humectant is further introduced into the system to prepare a "three-in-one" product, its salt resistance significantly decreases. This indicates that under the existing technology system, there is an irreconcilable contradiction between the product's functionalization (such as humectant) and core performance (salt resistance), making it difficult to simultaneously meet the application requirements of high salt resistance and multifunctionality.
[0004] Therefore, developing a sodium polyacrylate thickener that can overcome salt sensitivity defects, possess excellent shear-dilution behavior, and be compatible with other functions without significantly impairing core performance has significant industrial application value. Summary of the Invention
[0005] To address the problems of poor salt resistance, insufficient shear dilution in high salt resistance technology, and difficulty in functional integration and synergistic performance of existing sodium polyacrylate thickeners, the present invention aims to provide a sodium polyacrylate thickener with shear dilution and salt resistance, and its preparation method.
[0006] This invention constructs a dual network structure through the synergistic effect of a crosslinking agent and a hydrophobic modifier, and employs a specific UV photopolymerization process to effectively control the rheological behavior and salt ion responsiveness of the thickener while maintaining its high viscosity and good processability. This results in products with significant shear-dilution properties and excellent salt resistance. This thickener is suitable for applications requiring complex rheological control and high salt tolerance, such as coatings, cosmetics, and oilfield chemicals.
[0007] The objective of this invention is achieved through the following technical solution.
[0008] A method for preparing a sodium polyacrylate thickener with shear dilution and salt resistance includes the following steps: (1) Neutralization of acrylic acid: After diluting acrylic acid with pure water, it is neutralized with sodium hydroxide solution to a degree of neutralization of 70%-85% under the condition of temperature below 40℃, so as to obtain sodium acrylate neutralized solution with a solid content of 20%-45%. (2) Addition of crosslinking agent: Add crosslinking agent N,N'-methylenebisacrylamide to the neutralized solution obtained in step (1), the amount of which is 0.01%-0.5% of the mass of acrylic acid monomer, and stir to dissolve; (3) Introduction of hydrophobic modifier: Add hydrophobic modifier to the system obtained in step (2), wherein the hydrophobic modifier is at least one of alkyl acrylate or alkyl methacrylate with 12-18 carbon atoms, and the amount added is 0.1%-5.0% of the mass of acrylic monomer, and stir and mix evenly; (4) Addition of sodium sulfite: Add an aqueous solution of sodium sulfite to the mixture obtained in step (3). The amount of sodium sulfite added is 0.5%-5.0% of the mass of the acrylic acid monomer. (5) Ultraviolet light-initiated polymerization: The mixture obtained in step (4) is placed in an ultraviolet light reaction device and polymerized under ultraviolet light with a wavelength of 200-400 nm for 0.5-3 hours to obtain a gel-like product; (6) Post-processing of the product: The gel-like product obtained in step (5) is chopped, dried, pulverized and sieved to obtain a white powder of sodium polyacrylate thickener.
[0009] Furthermore, in the above preparation method, the degree of neutralization in step (1) is 75%-80%.
[0010] Furthermore, in the above preparation method, the amount of crosslinking agent N,N'-methylenebisacrylamide added is 0.05%-0.2% of the mass of the acrylic acid monomer.
[0011] Furthermore, in the above preparation method, the hydrophobic modifier is at least one of dodecyl methacrylate, tetradecyl methacrylate, hexadecyl methacrylate, or octadecyl methacrylate, and the amount added is 0.5%-2.0% of the mass of the acrylic monomer.
[0012] Furthermore, in the above preparation method, sodium sulfite is added in step (4) in the form of an aqueous solution with a mass concentration of 5%-20%.
[0013] Furthermore, in the above preparation method, the ultraviolet light source in step (5) is a high-pressure mercury lamp, the irradiation distance is 10-30 cm, and the irradiation time is 1-2 hours.
[0014] The present invention also discloses a sodium polyacrylate thickener with shear dilution and salt resistance, which is prepared by the method described in any of the above-mentioned methods.
[0015] Furthermore, the above-mentioned sodium polyacrylate thickener, in its 0.2wt% aqueous solution, meets the following performance indicators: viscosity at 6 rpm is 1500-3000 mPa•s; viscosity retention rate is ≥40% after adding 0.15wt% NaCl; and its shear dilution index is 2.0-10.0, wherein the shear dilution index is the ratio of viscosity at 6 rpm to viscosity at 60 rpm.
[0016] This invention also discloses a method for preparing a three-in-one sodium polyacrylate thickener possessing shear dilution, salt resistance, and moisture retention properties, characterized by comprising the following steps: (a) Prepare a sodium acrylate mixture that has been added to all raw materials but has not undergone ultraviolet light polymerization according to steps (1) to (4) of claim 1; (b) Add a humectant to the mixture obtained in step (a), wherein the humectant is at least one of xanthan gum, pregelatinized starch, hydroxyethyl cellulose, sodium hyaluronate or trehalose, and the amount added is 0.2%-5.0% of the mass of acrylic monomer, and stir until uniform; (c) The mixture obtained in step (b) is placed under ultraviolet light for polymerization reaction. After the reaction is completed, it is chopped, dried and pulverized to obtain the three-in-one sodium polyacrylate thickener.
[0017] The present invention also discloses a three-in-one sodium polyacrylate thickener with shear dilution, salt resistance and moisture retention properties, which is prepared by the above method.
[0018] Compared with existing technologies, the present invention has the following advantages and beneficial effects: 1. Significantly improved salt resistance: By constructing a dual chemical-physical network, the attack of salt ions on the polyelectrolyte backbone is effectively shielded, allowing the product to maintain a high viscosity retention rate in salty environments and a wider applicable salt concentration range. 2. Achieved intelligent rheological control: The product exhibits significant shear dilution properties, facilitating processing and application. Furthermore, it rapidly recovers viscosity after shear stress relief, balancing processing performance and application stability. 3. Good process feasibility and compatibility: The preparation method is based on UV photopolymerization, with mild and easily controllable conditions. The resulting product demonstrates good compatibility and storage stability in complex application systems (such as emulsion coatings), facilitating industrialization. 4. Strong functional scalability: While maintaining core salt resistance and rheological properties, functional components such as moisturizing agents can be easily introduced to prepare multifunctional composite products, meeting diverse needs. Attached Figure Description
[0019] Figure 1 This is a flow chart of the preparation process of the sodium polyacrylate thickener described in this invention; Figure 2 The results show the viscosity and salt resistance test results of different samples; Figure 3 The results of shear dilution and recovery tests for different samples; Figure 4 The relative viscosity (%) of the samples at different salt concentrations. Detailed Implementation
[0020] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below. However, it should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of the invention. Furthermore, descriptions of well-known structures and technologies are omitted in the following description to avoid unnecessarily obscuring the concept of the invention. All raw materials used in the embodiments of this invention are commercially available.
[0021] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present invention will now be described in detail with reference to the embodiments.
[0022] Example 1 A sodium polyacrylate thickener with shear dilution and salt resistance is prepared by the following steps: (1) Acrylic acid neutralization: Weigh 100 parts by weight of acrylic acid, add 180 parts by weight of pure water to dilute, and slowly add 30% sodium hydroxide solution to the system until the pH value is 6.8 under the cooling of ice water bath. The temperature of the neutralization process is controlled below 35℃, and finally a sodium acrylate neutralized solution with a neutralization degree of 78% and a solid content of 32% is obtained.
[0023] (2) Addition of crosslinking agent: Add 0.08% of N,N'-methylenebisacrylamide by mass of acrylic monomer to the neutralized solution obtained in step (1) and stir at room temperature until completely dissolved.
[0024] (3) Introduction of hydrophobic modifier: Add 1.2% of hexadecyl methacrylate by mass of acrylic monomer to the system obtained in step (2) and stir to mix evenly.
[0025] (4) Addition of sodium sulfite: Add a 20% sodium sulfite aqueous solution to the mixture obtained in step (3), wherein the amount of sodium sulfite added is 1.5% of the mass of acrylic acid monomer, and stir evenly.
[0026] (5) Ultraviolet light-initiated polymerization: The mixture obtained in step (4) is transferred to a quartz reactor and placed under a high-pressure mercury lamp with a wavelength of 365nm. The distance between the lamp tube and the liquid surface is kept at 15cm. The ultraviolet light is turned on for polymerization for 1.5 hours to obtain a transparent gel product.
[0027] (6) Post-processing of the product: The obtained gel-like product is chopped, dried in an 85°C forced-air drying oven to constant weight, pulverized and passed through a 120-mesh sieve to obtain a white powder thickener.
[0028] Example 2 A sodium polyacrylate thickener with different amounts of crosslinking agent Based on Example 1, the raw material composition was adjusted as follows, while the remaining preparation steps remained the same: In step (2), the amount of N,N'-methylenebisacrylamide added is adjusted to 0.15% of the mass of the acrylic acid monomer.
[0029] In step (3), the amount of hexadecyl methacrylate added is adjusted to 0.8% of the mass of acrylic monomer.
[0030] In step (4), the amount of sodium sulfite added is adjusted to 2.0% of the mass of acrylic acid monomer.
[0031] Example 3 Sodium polyacrylate thickener with different hydrophobic modifiers Based on Example 1, the raw material composition was adjusted as follows, while the remaining preparation steps remained the same: In step (3), the hydrophobic modifier is replaced with an equal amount of tetradecyl methacrylate.
[0032] In step (4), the amount of sodium sulfite added is adjusted to 1.0% of the mass of acrylic acid monomer.
[0033] Example 4 A three-in-one sodium polyacrylate thickener with shear-dilution, salt resistance, and moisture retention properties. Its preparation method includes the following steps: (a) Following steps (1) to (4) of Example 1, a sodium acrylate mixture with all raw materials added but not subjected to UV polymerization was prepared.
[0034] (b) Add xanthan gum (prepared as a 5% aqueous solution and fully swollen) at 1.0% of the mass of acrylic monomer to the mixture obtained in step (a) and stir until homogeneous.
[0035] (c) The mixture obtained in step (b) is placed under ultraviolet light and polymerized according to the conditions of step (5) in Example 1. After the reaction is completed, it is chopped, dried and pulverized to obtain the three-in-one thickener.
[0036] Comparative Example 1 Based on Example 1, N,N'-methylenebisacrylamide is not added in step (2), while the other raw materials and preparation methods remain unchanged.
[0037] Comparative Example 2 Based on Example 1, no hexadecyl methacrylate is added in step (3), while the other raw materials and preparation methods remain unchanged.
[0038] Comparative Example 3 Based on Example 1, in step (4), sodium sulfite is not added. Instead, 0.03% of the mass of acrylic monomer, 2-hydroxy-2-methyl-1-phenyl-1-propanone, is added as a conventional UV photoinitiator. The remaining steps remain the same.
[0039] Comparative Example 4 Based on Example 1, the ultraviolet irradiation in step (5) was removed and replaced with thermally initiated polymerization in a 60°C water bath for 3 hours, while the remaining steps remained the same.
[0040] Test Example 1: Thickener viscosity and salt resistance test Test objective: To verify the effect of the sodium polyacrylate thickener of the present invention on basic thickening performance and salt resistance, thickener samples prepared in Examples 1–3 and Comparative Examples 1–4 were selected to test their apparent viscosity and viscosity retention rate in the presence of salt.
[0041] Test Method: Each sample was prepared into an aqueous solution with a solid content of 0.2 wt%, and allowed to swell at 25°C for 24 hours. The apparent viscosity (η0) was measured using a Brookfield DV2T viscometer with an SC4-21 rotor at 6 rpm. Subsequently, NaCl was added to each solution to a concentration of 0.15 wt%, stirred thoroughly, and allowed to stand for 30 minutes. The viscosity (η1) was then measured under the same conditions. The viscosity retention rate (μ) was calculated using the formula: μ (%) = (η1 / η0) × 100%. All samples were measured in triplicate, and the average value was taken.
[0042] Test data are shown in Table 1 and Figure 2 .
[0043] Table 1. Viscosity and salt resistance test results of different samples.
[0044] As shown in Table 1, Examples 1 and 2 exhibited high initial viscosity and outstanding salt resistance (μ>51%), while Example 3 had a slightly lower viscosity retention rate but was still significantly better than most comparative examples. Comparative Example 1 (without crosslinking agent) and Comparative Example 3 (with conventional initiator) showed the worst salt resistance (μ<30%), indicating that the chemical crosslinking network and the specific initiation system of this invention are crucial for resisting salt ion attack. Comparative Example 2 (without hydrophobic modifier) had the lowest initial viscosity and moderate salt resistance.
[0045] Test Example 2: Shear dilution and recovery test Test objective: To evaluate the rheological behavior of different thickener samples, especially their shear dilution characteristics and structural recovery ability after shear cessation.
[0046] Test method: The sample was prepared into a 0.2 wt% aqueous solution, swollen, and then tested using a rheometer at 25°C. Test procedure: Shear rate from 0.1 s⁻¹ -1 Linearly increase to 100 s -1 Recorded in 6 seconds -1 and 60 s -1 Based on the apparent viscosity, calculate the shear dilution index (SDI) = η(6 s). -1 ) / η (60 s -1 ). Then, in 100 s -1 Apply high shear for 60 seconds, then immediately reduce the shear rate to 0.1 s. -1 The time required for the viscosity to recover to 90% of its equilibrium viscosity is the recovery time.
[0047] Test data are shown in Table 2 and Figure 3 .
[0048] Table 2. Results of shear dilution and recovery tests for different samples
[0049] Results Analysis: The samples in the embodiments of this invention exhibit significant shear dilution (SDI 2.91-4.14) and rapid structural recovery (recovery time <35 s). This is likely due to the synergistic effect of the elastic recovery provided by the chemical cross-linking network and the dynamic shear response provided by the hydrophobic associative physical network. Comparative Examples 1 and 3, while exhibiting some shear dilution, have extremely long recovery times, indicating that their structures are difficult to rebuild after damage and lack an effective elastic recovery network. Comparative Example 2 has a lower SDI and moderate recovery.
[0050] Test Example 3: Performance stability test at different salt concentrations.
[0051] Test objective: To examine the thickener's ability to retain performance over a wider range of salt concentrations and to verify its broad applicability in salt resistance.
[0052] Test method: Select representative samples, prepare 0.2 wt% solutions, and add NaCl to make salt concentrations of 0%, 0.15%, 0.5%, and 1.0%, respectively. After swelling equilibrium, measure the apparent viscosity at 6 rpm and calculate the percentage of viscosity at each salt concentration relative to the viscosity of the sample in pure water (relative viscosity).
[0053] Test data are shown in Table 3 and Figure 4 .
[0054] Table 3. Relative viscosity (%) of samples at different salt concentrations.
[0055] Results Analysis: With increasing salt concentration, the viscosity of all samples decreased, but the magnitude of the decrease varied significantly. The relative viscosities of Examples 1 and 4 at all salt concentrations were significantly higher than those of the comparative examples. In a high-salt environment of 1.0%, Example 1 maintained more than a quarter of its initial viscosity in thickening capacity, while Comparative Example 3 lost more than 90% of its thickening capacity. Example 4 showed the same trend as Example 1.
[0056] Test Example 4: Application compatibility and storage stability testing Test objective: To simulate real-world application environments and evaluate the compatibility and storage stability of thickeners in complex systems.
[0057] Test method: The sample was added to an acrylic emulsion coating at a dosage of 0.5% and dispersed uniformly at high speed. Initial compatibility was observed. Subsequently, the coating was placed in a 50°C oven for accelerated storage for 7 days, and changes in its state were observed and the rate of change of its Stormer viscosity (KU) value was tested.
[0058] The test data is shown in Table 4.
[0059] Table 4. Compatibility and storage stability of the samples in coatings.
[0060] As shown in Table 4, the product of this invention exhibits excellent compatibility and storage stability in emulsion coatings, with only slight positive fluctuations in the KU value and a homogeneous system. In contrast, Comparative Examples 1 and 3 show problems such as poor compatibility, water separation during storage, and a significant decrease in viscosity.
[0061] The above series of tests demonstrate that this invention, by introducing specific crosslinking agents and hydrophobic modifiers and employing a sodium sulfite / UV initiation system, successfully prepared a sodium polyacrylate thickener possessing excellent salt resistance, significant shear dilution resistance, and rapid structural recovery. Test Examples 1-3 prove that the product maintains a high viscosity retention rate over a wide salt concentration range, resolving the contradiction between processability and stability in traditional products. Test Example 4 preliminarily verifies its good compatibility and storage stability in complex systems. Furthermore, introducing a humectant into the basic formulation yields a functionalized three-in-one product, while maintaining its core rheological and salt resistance properties. Overall, the comprehensive performance of the product of this invention is significantly superior to that of products produced using traditional processes and comparative products lacking key components.
[0062] The above embodiments and test examples are only used to illustrate the technical solutions of the present invention, and are not intended to limit the scope of protection of the present invention. Any equivalent substitutions or modifications made by those skilled in the art to the present invention without departing from the concept of the present invention should fall within the scope of protection of the present invention.
Claims
1. A method for preparing a three-in-one sodium polyacrylate thickener possessing shear dilution, salt resistance, and moisture retention properties, characterized in that, Includes the following steps: (1) Neutralization of acrylic acid: After diluting acrylic acid with pure water, it was neutralized with sodium hydroxide solution to a degree of neutralization of 78% at a temperature below 40°C, resulting in a sodium acrylate neutralized solution with a solid content of 20%-45%. (2) Addition of crosslinking agent: Add crosslinking agent N,N'-methylenebisacrylamide to the neutralized solution obtained in step (1), the amount of which is 0.08% of the mass of acrylic acid monomer, and stir to dissolve; (3) Introduction of hydrophobic modifier: Add a hydrophobic modifier to the system obtained in step (2), wherein the hydrophobic modifier is hexadecyl methacrylate, and the amount added is 1.2% of the mass of acrylic monomer, and stir to mix evenly; (4) Sodium sulfite added: Add sodium sulfite aqueous solution to the mixture obtained in step (3). The amount of sodium sulfite added is 1.5% of the mass of acrylic acid monomer. Sodium sulfite is added in the form of an aqueous solution with a mass concentration of 5%-20%. (5) Addition of humectant: Add a humectant to the mixture obtained in step (4), wherein the humectant is xanthan gum, and the xanthan gum is added in the form of a 5% mass concentration aqueous solution, and the amount of xanthan gum added is 1.0% of the mass of acrylic monomer, and stir evenly; (6) Ultraviolet light-induced polymerization: The mixture obtained in step (5) was placed in an ultraviolet light reaction device and polymerized for 1.5 hours under ultraviolet light irradiation with a wavelength of 200-400 nm. The ultraviolet light source was a high-pressure mercury lamp and the irradiation distance was 15 cm to obtain a gel-like product. (7) Product post-processing: The gel-like product obtained in step (6) is chopped, dried, pulverized, and sieved to obtain a white powdery sodium polyacrylate thickener.
2. A three-in-one sodium polyacrylate thickener possessing shear-dilution, salt resistance, and moisture-retaining properties, characterized in that, It is prepared by the method described in claim 1.
Citation Information
Patent Citations
New method for synthesizing high-viscosity salt-tolerant sodium polyacrylate thickening agent and preparation of three-in-one thickening agent
CN119371581A